Metode Pelaksanaan Pekerjaan Jalan (Proyek Pembangunan Jalan Jodipati (STA 0+000 ~ 0+670.25) dan Jalan Garboruji (STA 0+450 ~ 0+850) - Umi Rahayu (JERA : Journal of Engineering Research and Application, 2024)
The increasing number of factories in the Kendal Industrial Area means that the need for facilities and infrastructure such as roads is increasingly needed for vehicle routes for factory workers and interested people, apart from that. Apart from that, the implementation of this development is the final form of road building construction that meets the quality, quantity, cost and timeliness of its implementation technically and administratively in accordance with the contract documents and is well received by the budget user/Budget user's Authorized Person, the Commitment Making Officer/ official implementing technical activities.  In this project, many types of work are carried out, such as: Subgrade, Lower Foundation Layer (LPB), Upper Foundation Layer (LPA), Prime Coat, Tack Coat, Asphal. The focus of the observations made is the structure of road construction and also quality control of a road construction project.